2012
DOI: 10.1177/0956797612449176
|View full text |Cite
|
Sign up to set email alerts
|

Treating Thoughts as Material Objects Can Increase or Decrease Their Impact on Evaluation

Abstract: In Western dualistic culture, it is assumed that thoughts cannot be treated as material objects; however, language is replete with metaphorical analogies suggesting otherwise. In the research reported here, we examined whether objectifying thoughts can influence whether the thoughts are used in subsequent evaluations. In Experiment 1, participants wrote about what they either liked or disliked about their bodies. Then, the paper on which they wrote their thoughts was either ripped up and tossed in the trash or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
76
0
11

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(95 citation statements)
references
References 38 publications
8
76
0
11
Order By: Relevance
“…After describing how physical objects can influence our thoughts, this section examines how our thoughts can be treated as physical objects. In a recent set of studies on thought objectification, Briñol, Gascó, Petty, and Horcajo () examined this question empirically by studying the extent to which people can move from metaphorical analogies of thought to a more literal view of thoughts as physical objects. We began by asking European participants to write down either positive or negative thoughts about the Mediterranean diet on a piece of paper.…”
Section: Part Ii: Mind–objectmentioning
confidence: 99%
See 1 more Smart Citation
“…After describing how physical objects can influence our thoughts, this section examines how our thoughts can be treated as physical objects. In a recent set of studies on thought objectification, Briñol, Gascó, Petty, and Horcajo () examined this question empirically by studying the extent to which people can move from metaphorical analogies of thought to a more literal view of thoughts as physical objects. We began by asking European participants to write down either positive or negative thoughts about the Mediterranean diet on a piece of paper.…”
Section: Part Ii: Mind–objectmentioning
confidence: 99%
“…In one of the studies in this series, participants first had to write positive or negative thoughts about increasing their level of physical exercise. Then, all participants were asked to move what they wrote to a box labelled as a ‘trash can’ (conceptually similar to Briñol et al ., ) or as a ‘safety box’. The results showed that physically moving objectified thoughts to a trash can led them to be mentally discarded as well, whereas physically moving them to a safety box led them to be relied upon more, even though the physical action was the same in both conditions.…”
Section: Part Ii: Mind–objectmentioning
confidence: 99%
“…A number of abstract constructs have been considered as a part of the self. These include a person's arguments (De Dreu & Van Knippenberg, 2005), attitudes (Abelson & Prentice, 1989;Mead, 1913;Sherif & Cantril, 1947), beliefs (Abelson, 1986;Cooley, 1902;Prelinger, 1959), opinions (M. B. Smith, Bruner, & White, 1956, thoughts (Briñol, Gascó, Petty, & Horcajo, 2013), and values (Csikszentmihályi & Rochberg-Halton, 1981). Importantly, the degree that these thoughts have integrated with one's self-concept likely vary.…”
Section: Thoughtsmentioning
confidence: 99%
“…In a separate line of research, Brinol et al [10] asked participants to write their likes and dislikes relating to their physical bodies on a piece of paper. The researchers found that those individuals who then tore up and discarded this paper relied less upon those thoughts in forming subsequent judgements than those who kept them, and that this effect was enhanced if the retained paper was kept in a safe place (i.e., in a participant's pocket).…”
Section: Work-in-progress: Poster Presentationmentioning
confidence: 99%
“…In another experiment by Brinol et al [10], the authors found evidence that these effects were stronger when a physical action was performed rather than simply imagined, and Xu et al [9] reported that physically undertaking an act (washing hands) was more effective than simply watching the act on a video. This therefore suggests that facilitating the (physical) expression of such empathetic concern has the potential to have positive psychological benefits for those involved.…”
Section: Work-in-progress: Poster Presentationmentioning
confidence: 99%